Underworld - Cabot, Meg. (New York : Point, 2012)
John Hayden, a death deity, takes seventeen-year-old Pierce Oliviera back to the Underworld against her will to keep her safe from the Furies, but her family is still at risk and she, herself, may never escape his captivity.
"An Abandon novel"--Cover.
Keywords: Supernatural -- Fiction; Gods -- Fiction; Mythology, Greek -- Fiction; Erinyes (Greek mythology) -- Fiction; Future life -- Fiction; Family life -- Florida -- Fiction; JUVENILE FICTION / Social Issues / Dating & Sex; JUVENILE FICTION / Love & Romance; JUVENILE FICTION / Legends, Myths, Fables / Greek & Roman; Florida -- Fiction